2021
DOI: 10.1186/s13643-021-01719-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved couple satisfaction and communication with marriage and relationship programs: are there gender differences?—a systematic review and meta-analysis

Abstract: Background The aspects of marriage and relationship and their effect on couples’ satisfaction are essential and critical aspects to be explored in this globalized and contemporary world. Since there are no reported meta-analysis and systematic reviews conducted in the last two decades in this area, we aimed to investigate the effect of marriage and relationship programs (MRP) on couples’ relationship satisfaction (CRS) and couples’ relationship communication (CRC) and also to determine the gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Furthermore, the analyses revealed an interaction effect between time and gender, indicating that the levels of symptomatology and depression among women, but not men, had significantly reduced, and their parenting satisfaction had improved after therapy, with stability of these results at 6‐month follow‐up. This result is consistent with previous findings that suggest marriage and relationship programs lead to better outcomes in women compared to men (Javadivala et al, 2021). Previous findings also show that women are more likely to seek couple therapy than men and that they tend to report a greater number and severity of problems at the outset of therapy than men (R. B. Miller et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the analyses revealed an interaction effect between time and gender, indicating that the levels of symptomatology and depression among women, but not men, had significantly reduced, and their parenting satisfaction had improved after therapy, with stability of these results at 6‐month follow‐up. This result is consistent with previous findings that suggest marriage and relationship programs lead to better outcomes in women compared to men (Javadivala et al, 2021). Previous findings also show that women are more likely to seek couple therapy than men and that they tend to report a greater number and severity of problems at the outset of therapy than men (R. B. Miller et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Research has consistently demonstrated the effectiveness of family counseling in improving communication patterns and marital satisfaction (Javadivala et al, 2021;Oladipo et al, 2024). Meta-analytic studies have found that couples who participate in counseling experience significant improvements in relationship functioning, including increased satisfaction, reduced conflict, and enhanced communication skills.…”
Section: The Role Of Family Counseling In Addressing Communication Ch...mentioning
confidence: 99%
“…For example, interventions targeting sexual well-being in couples have been shown to improve not only aspects of positive sexuality such as fun, pleasure and comfort during sexual intercourse, but also emotional closeness and communication within the couple and relationship satisfaction ( Rosier and Tyler, 2017 ; De Santis et al, 2019 ). Similarly, couple-based programs addressing issues related to emotional closeness and communication barriers can result in significant improvements in sexual intimacy and satisfaction ( Wiebe et al, 2018 ; Morgis et al, 2019 ; Javadivala et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%